2017
DOI: 10.18632/oncotarget.14754
|View full text |Cite
|
Sign up to set email alerts
|

Middle east respiratory syndrome corona virus spike glycoprotein suppresses macrophage responses via DPP4-mediated induction of IRAK-M and PPARγ

Abstract: Middle East Respiratory Syndrome Corona Virus (MERS-CoV) is transmitted via the respiratory tract and causes severe Acute Respiratory Distress Syndrome by infecting lung epithelial cells and macrophages. Macrophages can readily recognize the virus and eliminate it. MERS-CoV infects cells via its Spike (S) glycoprotein that binds on Dipeptidyl-Peptidase 4 (DPP4) receptor present on macrophages. Whether this Spike/DPP4 association affects macrophage responses remains unknown. Herein we demonstrated that infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
77
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(78 citation statements)
references
References 41 publications
0
77
0
1
Order By: Relevance
“…This could contribute to the level of pulmonary inflammation and tissue damage associated with MERS-CoV induced progressive pneumonia. On the other hand, recent studies in differentiated THP-1 macrophages infected with lentiviral particles pseudotyped with MERS-CoV S protein suggested that macrophage responses including IL-6 and TNF-α production were reduced, while LPS-induced production of the immunosuppressive IL-10 was increased (Al-Qahtani et al, 2017). This increase in IL-10 production was mediated by DPP4 binding and activation of IRAK-M, a negative regulator of TLR signaling and the transcriptional repressor PPARγ (Al-Qahtani et al, 2017).…”
Section: Mers-cov Virus Infects and Replicates In Human Macrophagesmentioning
confidence: 99%
See 3 more Smart Citations
“…This could contribute to the level of pulmonary inflammation and tissue damage associated with MERS-CoV induced progressive pneumonia. On the other hand, recent studies in differentiated THP-1 macrophages infected with lentiviral particles pseudotyped with MERS-CoV S protein suggested that macrophage responses including IL-6 and TNF-α production were reduced, while LPS-induced production of the immunosuppressive IL-10 was increased (Al-Qahtani et al, 2017). This increase in IL-10 production was mediated by DPP4 binding and activation of IRAK-M, a negative regulator of TLR signaling and the transcriptional repressor PPARγ (Al-Qahtani et al, 2017).…”
Section: Mers-cov Virus Infects and Replicates In Human Macrophagesmentioning
confidence: 99%
“…The MERS-CoV S protein DPP4 receptor is widely expressed in human cells including lower respiratory tract non ciliated bronchial epithelium, kidney epithelial cells, small intestine cells, T lymphocytes and macrophages (Al-Qahtani et al, 2017;Boonacker and Van Noorden, 2003;Tang et al, 2017;Widagdo et al, 2016). There is limited expression of DPP4 in the upper respiratory tract epithelium in humans when compared to dromedary camels, which may contribute to the limited replication of MERS-CoV in the human upper respiratory tract and to restriction of human-to-human transmission (Widagdo et al, 2016).…”
Section: Dpp4 Receptormentioning
confidence: 99%
See 2 more Smart Citations
“…These data indicate that dysregulated immune response-associated lung immunopathology in MERS-CoV-infected patients might lead to deleterious clinical manifestations. In addition, recent evidence (Al-Qahtani et al, 2017) showed that the capture of the human CD26 by MERS-CoV S protein suppressed macrophage responses via CD26-mediated induction of Toll-like receptor (TLR) signaling. This discovery verified our previous observation about the potential impact of both MERS-CoV and SARS-CoV on the host immune responses through interaction with their receptors (Liu et al, 2017b).…”
Section: T-cell Immunity To Mers-cov and The Cross-reactivity To Sarsmentioning
confidence: 99%